Estimation of Above Ground Carbon Stock at Above Reclamation Area of PT. ANTAM UBPE Pongkor, West Java Province - Lailan Syaufina; Muhammad Ikhsan (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2013)
Global Warming is one of the environmental issues that are currently flare hit many areas in the world. The impacts of global warming need to be minimized by mitigating of carbon emission, i.e. to to reduce emissions or increase sequestration of carbon and carbon stocks. Efforts to increase the absorption of carbon stocks and at the same time reducing greenhouse gases emissions has been indicated indirectly by reclamation on the post mining area. An important aspect to be studied is the potential of the carbon stored in the post mining reclamation area.. The objective of this study was to measure and calculate the above ground carbon stocks on the post mining reclamation area of PT. Antam UBPE Pongkor. The study was carried out using non-destructive method, which estimates the carbon content without cutting the trees by using parameters such as diameter at breast height and tree height. The study shows that the above ground of post mining reclamation area of PT. Antam UBPE Pongkor contains biomass amounted to 127.89 ton ha-1 and the carbon content of 58.77 ton ha-1. The result consist four potential of biomass, which is standing forest, litter, lower plants/shrubs and necromass with biomass of 122.75 ton ha-1, 2.45 ton ha-1, 1.28 ton ha-1, 1.41 ton ha-1 and 56.41 ton ha-1 respectively, and carbon content of 1.13 ton ha-1, 0.59 ton ha-1, 0.65 ton ha-1 respectively.Keywords: biomass. carbon stock, global warming, reclamation area